Funciones desempeñadas como supervisor de planillas y jefe de personal en la compañia de minas Buenaventura S.A.A. (Período 2013-2017) - Chávez Rojas, William Gustavo (2018)
The purpose of this professional proficiency report is to make known the current reality of the Compañía de Minas Buenaventura S.A. especially in the human resources department, the work carried out in this area and the improvement actions that were carried out in the following processes are described: recruitment plan, selection plan by competence, personal induction plan, evaluation plan of performance by competence and payrolls of the department of human resources, arriving at the following conclusions the current process of selection and hiring is more focused on the strategies and internal policies of the company. Another factor observed in the study process is the lack of a correct induction process. From this and after having studied and described the theory that refers to competency management, we can conclude that the management of human talent, in any company or institution that was, at the time of recruiting, selecting and evaluating a Effective way to staff gives a guideline to be able to design correctly the charges that the company requires. The selection of personnel can be variable, there are interviews that constitute a fundamental part for the selection process, which gives us a vision of the candidate to be selected, the test applications among others analyze in a deeper way the personality, the character and among other key factors for making the decision at the time of choosing the final candidate and this shows us the level of behavior in different scenarios. Therefore, I am aware that all the improvement actions that were carried out in the mining company had a positive effect and therefore the costs in the human resources department were optimized.